2017
DOI: 10.1103/physrevb.96.115426
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the topological states in metal-organic bilayers

Abstract: We have investigated the energetic stability and the electronic properties of metal-organic topological insulators bilayers (BLs), (MC4S4)3-BL, with M=Ni and Pt, using first-principles calculations and tight-binding model. Our findings show that (MC4S4)3-BL is an appealing platform to perform electronic band structure engineering, based on the topologically protected chiral edge states. The energetic stability of the BLs is ruled by van der Waals interactions; being the AA stacking the energetically most stabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In a previous study 17 , we verified that the occupation of the kagome bands, as well as the localization of the non-trivial energy gaps in MOF/MOF interfaces, can be controlled by an external electric field. It is worth to pointing out that the energy bands responsible to the QAH phase are completely spin polarized and separated, with the magnetization out of the MOF plane.…”
Section: Quantum Anomalous Hall Effectsupporting
confidence: 64%
See 1 more Smart Citation
“…In a previous study 17 , we verified that the occupation of the kagome bands, as well as the localization of the non-trivial energy gaps in MOF/MOF interfaces, can be controlled by an external electric field. It is worth to pointing out that the energy bands responsible to the QAH phase are completely spin polarized and separated, with the magnetization out of the MOF plane.…”
Section: Quantum Anomalous Hall Effectsupporting
confidence: 64%
“…Further molecular design has been done by building up multilayered systems by stacking MOFs [13][14][15][16] . Very recently, based on firstprinciples calculations, we have found that bilayer sys-tems of (MC 4 S 4 ) 3 , with M=Ni and Pt, present the Z 2metallic phase, where the edge states can be tuned by an EEF ⊥ 17 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in (NiC 4 S 4 ) 3 bilayers (2ML), the stacking geometry is characterized by the alignment of sites X and Y of the different layers (2ML-XY), with X and Y = A, B, G, and H, as indicated in Fig. 1 In a previous study [26], we have found the 2ML-AA configuration to be the most stable. There, the calculations were performed using the non-local vdW-DF2 [38] correction to describe the vdW interactions.…”
Section: A Stacking Geometrymentioning
confidence: 92%
“…Recently, it has been proposed a bending strain perturbation approach to control spin currents in 2DTIs [29]. Meanwhile, ensuing research has shown a) Electronic mail: felipe.lima@ufu.br layer localization control of topological states by an applied external electric field in MOF bilayer nanoribbons [26] and bilayer graphene grain boundaries [30]. Furthermore, the exploration of van de Waals heterostructures allows for designed properties by combining the stacking of two-dimensional materials [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for zero external field ν = 0, the Hamiltonian commutes with τ x (which coincide with the M z symmetry operator), and the eigenstates reduce to the mirror symmetric and antisymmetric cases g m = ±1. Moreover, for ν = 0 we can still separate the Hamiltonian into two orthogonal subspaces defined by its pseudomirror symmetry [41]…”
Section: B Control Of Orbital-texture In Coupled Bilayermentioning
confidence: 99%